The Impact of Transmigration on The Development of Christianization in West Pasaman (1953-1980) - Nelly Indrayani; Supian Ramli (Criksetra: Jurnal Pendidikan Sejarah, 2023)
This study reveals the social history of transmigration's effects on the chirstianization of pasaman. This chirstianization took place in 1953, for the existence of christians who have settled in about the 20th century. These christians came from java, and it's mainly in transmigration resettlement areas. In progress until the end of 1980, chirstian activity look dinamics, so that christian could engage in various activity of life. The study uses historical science research methods of heuristic, critisim, interpretation, and historiography. Studies have found that, the social movement of christian resulted from transmigration trough all walks of life in the pasaman. The christian movement in the pasaman included education, place of worship, youth and art, and socioeconomic society. A propesive action is that without resorting to anarchy in a persuasive or inviting approach. This effrot has brough various froms of infrastructure to all sector of life.